Temperature elevation measured in a tissue-mimicking phantom for transvaginal ultrasound at clinical settings. (February 2017) - Miloro, Piero; Martin, Eleanor; Shaw, Adam
Introduction: This paper reports the results of an audit to assess the possible thermal hazard associated with the clinical use of ultrasound scanners in UK Hospitals for transvaginal ultrasound imaging. Methods: An anatomically relevant phantom composed of a block of agar-based tissue mimicking material with embedded thermal sensors was developed. Seventeen hospitals around the UK were visited and a total of 64 configurations were tested. A representative typical scanning protocol was adopted, which primarily used B-mode with 30 s periods of colour-flow and pulsed Doppler modes for both gynaecology and obstetrics pre-sets. Results: The results confirmed that the highest temperature increase is always at the surface. The greatest temperature rise measured across all the systems was 3.6℃, with an average of 2.0℃ and 2.16℃ for gynaecology and obstetrics pre-sets, respectively. For some systems, the temperature increased rapidly when selecting one of the Doppler modes, so using them for longer than 30 s will in many cases lead to greater heating. It is also shown that, in agreement with previous studies, the displayed thermal index greatly underestimates the temperature rise, particularly close to the transducer face but even to distances approaching 2 cm. Conclusions: Overall, the results of the audit for the temperature rise during transvaginal ultrasound at clinical settings fell within the limits indicated by the national and international standards, for the pre-sets tested and following a representative typical scanning protocol. Only selected pre-sets were tested and the scanner outputs were not maximised (for example by using zoom, greater depth or narrow sector angles). Consequently, higher temperatures than those measured can certainly be achieved.